Automatização de processos para a produção de documentos cartográficos e de ordenamento territorial: zoneamento agroambiental aplicado à Bacia Hidrográfica do Ribeirão do Feijão – SP - Ruggiero, Mayara Herrmann (2022)
The territorial planning instruments are essential to identify and reduce the environmental impacts caused by human activity. Computational models and methods applied to the production of cartographic documents for analysis and territorial planning, can contribute with the dynamics for its elaboration and application, mostly in areas with relevant environmental characteristics. In this research the aim was the development and application of methods and computational models integrated with ArcGIS software. These models and methods must perform the process to obtain environmental maps and charts, resulting in an agrienvironmental planning chart to the Ribeirão do Feijão watershed, located at the central region of the state of São Paulo. The research was divided in some principal stages: the first one focused on data collection and geographic treatment; the second on the elaboration of intermediaries documents, which were used to the final analysis, with process automation in GIS environment; being these: anthropic use transition potential chart; aquifer contamination potential chart; surface runoff potential chart; legal restrictions charts and; agricultural potential chart. Finally, the model which combines all these documents was developed for the elaboration of the agrienvironmental planning chart for Ribeirão do Feijão watershed, with the definition of planning units and its guidelines. With the development and application of the land use change analysis model, it was observed that in the watershed there was an increase in agricultural areas to the detriment of native vegetation. The anthropic use transition potential chart showed that the medium potential predominates in the study area, however the high and very high potentials together occupy 42.86% of the area. The mapping and analysis of legal restrictions indicated that there is a deficit of native vegetation coverage in permanent preservation areas and legal reserves. Regarding the aquifers contamination potential, between 1985 and 2019, the watershed showed an increase of 11.78% in areas with high potential and 58.14% with very high potential. The surface runoff potential chart showed that the low potential class appears with distinction in the study area, occupying approximately 50% of the region in 2019. However, between 1985 and 2019 there was an increase of 37.47% in the high and very high potential classes.The agricultural potential chart was important for identify regions with favorable characteristics for cultivation. In the study area there is a predominance of medium potential, and 12% of the area has high or very high potential. With the elaboration and analysis of the mentioned documents, the agrienvironmental planning was elaborated for the Ribeirão do Feijão watershed. Six homogeneous units were defined, each one with its characteristics and guidelines. In the watershed there are areas with native vegetation that need to be preserved, following the legislation, as well as areas that must be recovered, in order to observe the legal requirements. The geoenvironmental characteristics of the study area give the basin a need to control the anthropic activities. Therefore, guidelines that will encourage the increase of restoration areas, as well as those indicative of activities with reduced impact, are essential for the maintenance of the development, but with the promotion of the conservation of resources